Pendidikan Kesehatan Menggunakan Metode Audiovisual dalam Meningkatkan Pengetahuan Ibu Merawat Anak dengan Stunting - Fadyllah, Muhammad Ilham; Prasetyo, Yoyok Bekti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: Mother's knowledge is an important aspect to overcome stunting among children. Audiovisual health education is the best strategy to increase maternal knowledge. This study aimed to analyze the effects of health education using audiovisual methods in improving mothers' ability to care for children with stunting.Method: Data obtained from relevant databases. A systematic search for studies on health education using audiovisual media to increase mothers' knowledge in caring for children with stunting. The data was collected by searching for data based on article data published on the Scopus search, PubMed, Science Direct, Wiley Online Library. Articles screened using PRISM (Preferred. Reporting Items for Systematic. Reviews and Meta-analyses). The report is analyzed using the Nvivo software package version 12 plus (QSR International Inc., Burlington, MA, the USA with a matrix framework).Results: The use of audiovisuals in health education can increase mothers' knowledge in caring for children with chronic nutrition or stunting. The audiovisual information about stunting was delivered in some methods, such as education classes, TV commercials, health education, and online video. The video duration was about 5-6 minutes.